Physical and biogeochemical controls of the carbonate system of the Yucatan Shelf. (15th July 2022) - Barranco, Linda M.; Martín Hernández Ayón, J.; Pech, Daniel; Enriquez, Cecilia; Herrera, Jorge; Mariño, Ismael; Carlos Herguera, Juan
Abstract: The dynamics and distribution of the carbonate system and the processes that regulate it over the Yucatan Shelf (YS), a region of karst geology and high productivity that is influenced by submarine groundwater discharges (SGDs) and upwelling, were explored with data from two oceanographic cruises. The first oceanographic cruise was conducted in November 2015 during the Nortes season, a period of intense northerly wind activity, and a second cruise was conducted during the rainy season in August/September 2016. Notable biogeochemical differences were present between them. At the surface, Caribbean Surface Water (CSW) predominated over the shelf in both periods. During the Nortes cruise, a surface nearshore-offshore gradient showed high dissolved inorganic carbon (DIC; ∼2470 μmol kg −1 ) and total alkalinity (TA; ∼2460 μmol kg −1 ) values near the coast and average pHTotal and pCO2 values of 7.42 ± 0.10 and 2206 ± 546 μatm, respectively. These geochemical characteristics were attributed to the influence of SGDs, punctuated by relatively low δ 13 CDIC values between −4.18‰ and −2.49‰, which reflects an important oxidation of organic carbon and the dissolution of carbonate minerals. The presence of upwelled water on the eastern side of the YS showed average DIC and pHTotal values of 2260 ± 15 μmol kg −1 and 7.69 ± 0.08, respectively, which were lower than coastal values. During the rainy cruise, the advection of CSW by the Yucatan Current was traced by its thermohaline properties. However, the surface water carbonate system was relatively homogeneous, with average DIC, TA, pHTotal, and pCO2 values of 2047 ± 16 μmol kg −1, 2388 ± 11 μmol kg −1, 8.02 ± 0.02, and 440 ± 27 μatm, respectively. Lastly, the δ 13 CDIC values during this cruise ranged from −1.21‰ to 1.25‰, which suggests that the carbonate system is mainly regulated by organic matter production and respiration. Highlights: The carbonate system (CS) of the Yucatan Shelf remains inadequately characterized. CS variation depends on water mass advection and submarine groundwater discharge. The CS is influenced by seasonality. Organic matter respiration and CaCO3 dissolution influenced the CS in Nortes season. Caribbean Surface Water and high evaporation influenced the CS in the rainy season.